Path Integral Spin Dynamics for Quantum Paramagnets - Thomas Nussle; Pascal Thibaudeau; Stam Nicolis (Advanced Physics Research)
Abstract A path integral method, combined with atomistic spin dynamics simulations, is developed to calculate thermal quantum expectation values using a classical approach. In this study, it is shown how to treat Hamiltonians with non‐linear terms, that are relevant for describing uniaxial anisotropies and mechanical constraints. These interactions can be expressed solely through quadratic terms of the spin operator along one axis, that can be identified with the quantization axis.